The Use of Copper Oxides as Cross-Linking Substances for Chloroprene Rubber and Study of the Vulcanizates Properties. Part II. The Effect of Filler Type on the Properties of CR Products - Aleksandra Smejda-Krzewicka (MDPI AG, 2021)
The properties of rubber materials are dependent on the characteristics of the elastomer matrix, the filler type, the cross-linking agent, the number of ingredients, and their interactions. In the previous article, we showed that chloroprene rubber can be efficiently cross-linked with copper(I) oxide or copper(II) oxide. During the processing of rubber compounds, the incorporation of a filler and a curing substance are two substantial parameters, such as the homogeneity of mixing and cross-linking that significantly affect the properties of the vulcanizates. Therefore, this work aimed to evaluate the curing characteristics, mechanical and dynamical properties, morphology, and flammability of the composites containing chloroprene rubber cross-linked with Cu2O or CuO and filled with different fillers (silica, carbon black, montmorillonite, kaolin, chalk). It was found that the type of filler and curing agent had a significant impact on the degree of cross-linking of the chloroprene rubber and the properties of its vulcanizates. The degree and speed of the cross-linking of filled CR were higher when the CR was cured with copper(II) oxide. Among the fillers used, the presence of carbon black or silica ensured the highest degree of CR cross-linking and the most useful properties. The flammability tests indicated that all produced vulcanizates were characterized by a high oxygen index, which allows them to be classified as non-flammable materials.